Dosimetric Feasibility Study of Dose Escalated Stereotactic Body Radiation Therapy (SBRT) in Locally Advanced Pancreatic Cancer (LAPC) Patients: It Is Time to Raise the Bar - Mazzarotto, Renzo; Simoni, Nicola; Guariglia, Stefania; Rossi, Gabriella; Micera, Renato; De Robertis, Riccardo; Pierelli, Alessio; Zivelonghi, Emanuele; Malleo, Giuseppe; Paiella, Salvatore; Salvia, Roberto; Cavedon, Carlo; et al. (Frontiers in Oncology, 2020)
Background and Objective: To assess the dosimetric feasibility of a stereotactic body radiotherapy (SBRT) dose escalated protocol, with a simultaneous integrated boost (SIB) and a simultaneous integrated protection (SIP) approach, in patients with locally advanced pancreatic cancer (LAPC). Material and Methods: Twenty LAPC lesions, previously treated with SBRT at our Institution, were re-planned. The original prescribed and administered dose was 50/30/25 Gy in 5 fractions to PTVsib (tumor-vessel interface [TVI])/PTVt (tumor volume)/PTVsip (overlap area between PTVt and planning organs at risk volume [PRVoars]), respectively. At re-planning, the prescribed dose was escalated up to 60/40/33 Gy in 5 fractions to PTVsib/PTVt/PTVsip, respectively. All plans were performed using an inspiration breath hold (IBH) technique and generated with volumetric modulated arc therapy (VMAT). Well-established and accepted OAR dose constraints were used (D0.5cc < 33 Gy for luminal OARs and D0.5cc < 38 Gy for corresponding PRVoars). The primary end-point was to achieve a median dose equal to the prescription dose for the PTVsib with D98≥ 95% (95% of prescription dose is the minimum dose), and a coverage for PTVt and PTVsip of D95≥95%, with minor deviations in OAR dose constraints in < 10% of the plans. Results: PTVsib median (±SD) dose/D95/conformity index (CI) were 60.54 (±0.85) Gy/58.96 (±0.86) Gy/0.99 (±0.01), respectively; whilst PTVt median (±SD) dose/D95 were 44.51 (±2.69) Gy/38.44 (±0.82) Gy, and PTVsip median (±SD) dose/D95 were 35.18 (±1.42) Gy/33.01 (±0.84) Gy, respectively. With regard to OARs, median (±SD) maximum dose (D0.5cc) to duodenum/stomach/bowel was 29.31 (±5.72) Gy/25.29 (±6.90) Gy/27.03 (±5.67) Gy, respectively. A minor acceptable deviation was found for a single plan (bowel and duodenum D0.5cc=34.8 Gy). V38 < 0.5 cc was achieved for all PRV luminal OARs. Conclusions: In LAPC patients SBRT, with a SIB/SIP dose escalation approach up to 60/40/33 Gy in 5 fractions to PTVsib/PTVt/PTVsip, respectively, is dosimetrically feasible with adequate PTVs coverage and respect for OAR dose constraints.